PENGGUNAAN PLATFORM EDMODO BERBASIS E-LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Hayatun Napsia R. Tangahu; Sumarno Ismail; Resmawan Resmawan (ALGORITMA: Journal of Mathematics Education, 2022)
This study aims to determine the effectiveness of using the edmodo platform based on e-learning on students mathematics learning outcomes on number pattern material. The research was carried out at SMP Negeri 1 Botupingge in the odd semester of the 2021/2022 academic year. This type of research is an experimental research using the quasi-experimental method. The research design used was a non-equivalent control group design involving 2 classes as the research sample, namely the experimental class and the control class which were given different treatment. The sample was selected using a purposive sampling technique with the number of students in each class as many as 25 students. The data collection technique used is the provision of tests including pre-test and post-test in the form of essays to obtain data on student learning outcomes. The results of the analysis with the t-test at a significance level of 0.05 indicate a difference between the learning outcomes of students who are taught using Edmodo and Google Meet. The average student learning outcomes using Edmodo is 77.64, which is higher than the average student learning outcomes using Google Meet at 67.72. Based on the results of the average N-Gain calculation, the gain value is 0.61. This shows that the effectiveness of using the Edmodo platform is in the medium category. This study measures student learning outcomes in the cognitive domain using the Edmodo platform, so it is hoped that who will conduct researcher further research on the use of the Edmodo platform in the affective domain or in other educational units.